Biofilm Density on the Electrode is Positively Correlated with the Bioelectricity of the Microbial Fuel Cell of Fisheries Wastewater - Bustami Ibrahim; Uju Uju; Alvindo Chrisna Mukti (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Microbial fuel cell (MFC) is a bioreactor utilizing bacteria as electrocatalysts to convert bioenergy from biomass into electrical energy. The aim of this research were to determine the effects of the electrode distance on the bacterial density and the electrical value generated by the MFC as well as to evaluate the ability of MFC in reducing the pollutant. Single chamber MFC system with various electrode distances including 2 cm, 4 cm, and 6 cm were assembled. The wastewater of fish pindang processing was used as the mediumfor the MFC. The results showed that the distance had no effect on the biofilm density of the electrode and the reduction of the wastewater pollutant load. However, the distance affected the electrical value of theMFC. Biofilm density on the MFC electrode after 120 hours was 0.65-6.46 CFU/ cm2. The highest voltage was obtained from the 6 cm electrode distance with the voltage 0.38±0.01 V. Positive correlation (R2 = 0.99)between microbial density and electricity produced at the cathode was observed, but weak at the anoda (R2 = 0.47). The MFC system could decrease the BOD value up to 50.78% and COD up to 33.29%, however the TAN value was increased to 6 mg/L.